Devising a fuzzy stakeholder model for optimizing the portfolio of projects at a fishing industrial enterprise taking risks into account - Likhosherst, Elena; Mazelis, Lev; Solodukhin, Konstantin (Eastern-European Journal of Enterprise Technologies, 2019)
The method for portfolio investment, allowing the formation of the optimal portfolio structure considering degrees of satisfaction of requirements of stakeholder groups, risks and uncertainty of external and internal environment, was proposed. The model that represents a fuzzy nonlinear programming problem was considered. The weighted average of project utility is used as objective function. The utilities of projects are multiplicative Cobb-Douglas type functions using, along with financial indicators, expert verbal evaluations of qualitative indicators of satisfaction of stakeholder requirements, converted into fuzzy numbers. Exponents in this function reflect the significance of stakeholders for the organization in terms of the existing resource sharing between a company and a stakeholder and the degree of mutual influence. Quantitative accounting of risks is implemented based on the H. Markowitz approach and the scenario-based method. Uncertainty and lack of information for the indicator of economic efficiency of projects is modeled through the use of the fuzzy approach. Constraints in the model are also fuzzy. The transforming from a fuzzy optimization problem into a crisp problem is performed by assigning the satisfaction degrees for an objective function and the constraints. The choice of a certain satisfaction degree also makes it possible to some extent to take into account uncertainty, which, in turn, affects the composition of the portfolio. The solution to the model is found numerically using the proposed method, which allows, based on fuzzy utilities, finding fuzzy objective function and constraints, and transforming a fuzzy model into a crisp quadratic programming problem at specified satisfaction degrees. The example of the formation of an optimal portfolio of investment projects of a fishing industrial enterprise was explored.